PROBLEMS OF OPTIMIZING THE SOCIAL ENVIRONMENT IN A TEACHING COLLECTIVE (Web of Teachers: Inderscience Research, 2024)
The article focuses on the analysis of the pedagogical and psychological basis for creating a healthy environment in the community of educational institutions. Overcoming psychological tensions in the team, improving the professional skills of the head of the educational institution and subordinates, the proper organization of leisure time of employees, the opportunity to freely submit proposals for the organization of labor activities, team-friendly, as well as building partnerships.